2019
DOI: 10.1103/physrevapplied.11.064026
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Tunnel Field-Effect Transistor Based on a Complex-Oxide Lateral Heterostructure

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Heterostructures consisting of dissimilar materials have been the indispensable elements in modern electronics, including spin valve, [1] photovoltaics, [2] field-effect transistor, [3] energy harvester, [4] etc. Looking beyond conventional threedimensional (3D) semiconductors, creating two-dimensional (2D) heterostructures may provide unprecedented opportunities in device processing and engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Heterostructures consisting of dissimilar materials have been the indispensable elements in modern electronics, including spin valve, [1] photovoltaics, [2] field-effect transistor, [3] energy harvester, [4] etc. Looking beyond conventional threedimensional (3D) semiconductors, creating two-dimensional (2D) heterostructures may provide unprecedented opportunities in device processing and engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Müller et al have demonstrated a lateral heterostructure comprising a narrow STO channel between two LAO/STO contacts conducts at bias voltages significantly below 100 mV. [128] It is further demonstrated in the study that the tunnelling current can be easily controlled small gate-source voltages applied between a side gate and the channel. This study involving a [126] Copyright 2020, IOP Publishing Ltd.…”
Section: Field Effect Transistors and Beyondmentioning
confidence: 85%
“…To overcome this thermal subthreshold limit, a band-to-band tunneling field effect transistor (TFET) is developed in recent years. In contrast to conventional FETs, the primary mechanism in TFETs , is interband tunneling rather than thermal injection. Consequently, TFETs can achieve a steeper-subthreshold slope with SS < 60 mV/dev. Accordingly, the power consumption in TFETs can be effectively decreased. However, one challenge of TEFTs is that all fabricated TEFTs have severely limited ON-current.…”
Section: Introductionmentioning
confidence: 99%